The Syriac Life of Saint Maximus the Confessor and the Orthodox Tradition - Ерић, Бошко М (Sabornost - The Theological Year-book, 2013)
In this article the author represents The Syriac Life of Saint Maximus the Confessor. In the very beginning a problem of authorship is treated. Considering the name of the writer that is mentioned in The Life — Gregorios or Georgios, the author is trying closely to determine the identity of that historical figure. Afterwards the translation of The Life from the syriac language is given, as well as comparisons which include statements coming from The Orthodox Church tradition. In this chapter a difference between two traditions, Greek Orthodox tradition and Syriac Monothelite tradition, can be noticed in the view of St. Maximus the Confessor. The author also represents several most frequent objections concerning authenticity of the facts that are found in The Syriac Life, such as a question of origin, youth and education of Saint Maximus the Confessor.